Pengelolaan Lingkungan Alam Kereng Bangkirai Kota Palangka Raya Kalimantan Tengah - Muh. Azhari; Fahruddin Arfianto; Hariyadi; Mariaty (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2026)
The natural environment has an important role in maintaining the balance of the components in it, both biotic and abiotic components, the role of local culture that is full of meaning and religion so it needs to be managed well and its functions and conditions introduced to the community, especially gen z and gen alpha, for example, the natural environment in Kereng Bangkirai, Palangka Raya City, Central Kalimantan. The role of the natural environment in Kereng Bangkirai, Palangka Raya City includes being one of the producers of oxygen, a home for flora and fauna, tourism and education, so its sustainability needs to be maintained. Introduction to the natural environment is carried out using nature exploration techniques, and studying what is found in the environment, for example starting from low plants, shrubs, bushes, poles, stakes and trees. The results of the exploration obtained are predominantly low plants, shrubs and bushes and poles.